The most beautiful story - Tjønn, Brynjulf Jung, 1980- (Enchanted Lion Books, 2021)
Late at night, Vera runs to the pond where mysterious, blue-haired Syl tells a wonderful story to bring Vera's little brother, Salandar, back to life again.